Predicting Risk in Transcatheter Aortic Valve Implantation: Comparative Analysis of EuroSCORE II and Established Risk Stratification Tools - Silaschi, Miriam; Conradi, Lenard; Seiffert, Moritz; Schnabel, Renate; Schön, Gerhard; Blankenberg, Stefan; Reichenspurner, Hermann; Diemert, Patrick; Treede, Hendrik (The Thoracic and Cardiovascular Surgeon, 2015)
Background The logistic European System for Cardiac Operative Risk Evaluation (logEuroSCORE) II was developed to improve prediction of mortality in cardiac surgery. However, no specific tools are available for risk prediction in transcatheter aortic valve implantation (TAVI). The recently introduced EuroSCORE II was compared with established risk scores.Patients and Methods We assessed 457 consecutive patients (80.5 ± 7.1 years, 52.3% female) undergoing TAVI. Preoperative risk evaluation included logEuroSCORE I, EuroSCORE II, Society of Thoracic Surgeons (STS), Ambler, and Parsonnet scores. Validity was assessed by receiver-operating characteristic (ROC) and area under the curve (AUC).Results A 30-day mortality was 9.6% (44/457). Calculated scores were logEuroSCORE I 22.0%, confidence interval (CI) 21.0 to 24.6; EuroSCORE II 7.0%, CI 6.4 to 8.1; STS 7.9%, CI 7.7 to 9.5; Ambler score 6.9%, CI 5.7 to 7.0; and Parsonnet score 23.8%, CI 20.9 to 24.1. ROC analyses demonstrated no predictive value: logEuroSCORE I AUC 0.56, CI 0.47 to 0.65; EuroSCORE II AUC 0.54, CI 0.46 to 0.63; STS AUC 0.57, CI 0.49 to 0.66; Ambler AUC 0.52, CI 0.43 to 0.60; and Parsonnet AUC 0.51, CI 0.43 to 0.60. Accuracy and thresholds were measured on behalf of Youden index. Accuracy ranged between 44.2% (Parsonnet) and 66.3% (logEuroSCORE I). Thresholds were logEuroSCORE I 26%, EuroSCORE II 7%, STS 6%, Ambler 3%, and Parsonnet 19%.Conclusions No risk evaluation system provided acceptable predictive ability. Scores derived from conventional cardiac surgery failed in risk prediction for TAVI. Specific risk tools are required. Until available, estimation of risk has to rely on judgment of an interdisciplinary heart team regarding individual patient factors.
Keywords: transcatheter aortic valve implantation; aortic valve disease; aortic stenosis